Edukasi Senam Yoga dan Antenal Care Untuk Menurunkan Kecemasan Pada Masa Kehamilan - Agustine Ramie; Mahdalena Mahdalena; Ainun Sajidah; Hanifa Amira Aziza; Lutfia Lutfia; Nursyifa Nursyifa (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
In 2023, pregnant women in the working area of Puskesmas Martapura Timur mostly experienced anxiety in the face of childbirth. A total of 10 pregnant women with more than 20 weeks of pregnancy experienced mild anxiety 30%, moderate anxiety 50% and severe anxiety 20%. All pregnant women experienced low back pain and never received material about prenatal yoga during pregnancy. This community service expects pregnant women to increase knowledge and skills about Antenatal Care and yoga exercises to reduce anxiety during pregnancy. The method used is health counseling along with the game Ibu Hamil Ceria (MILRIA) with a peer group approach through pregnant women's classes. This activity was carried out 3 times a meeting of each prenatal class, totaling 9 meetings. When measuring anxiety levels in Pekauman village and Melayu Tengah village, it was found that 13 (61.9%) pregnant women experienced mild anxiety and the knowledge of pregnant women was lacking regarding ANC as many as 15 (71.4%) out of 21 people. So that health counseling and yoga exercises are carried out to reduce anxiety and increase knowledge in pregnant women. The results showed a decrease in anxiety levels to 31.2% and the knowledge of pregnant women increased to 81.2%.